Estudio de las Vulnerabilidades y Amenazas en la Red de Datos de la Facultad de Ciencias de la Salud de la UTB - Pilco Quispe, Cinthya Carolina (2018)
At present the computer sciences and specifically the computer and telecommunications industry have revolutionized all possible scenarios of work, education, training, television, telephony, aviation, automotive, telematics and health; maintaining a high impact on all segments of the human population. This is how the appearance of data networks has managed to collaborate with the evolution of all the disciplines and environments mentioned above, evidencing the participation of a work force taken from the English term Task Force (FT), the same one that indicates the work performed on an operation or mission in a concrete way. Therefore, we intend to contribute through this document a case study in which vulnerabilities and threats are described in the data network of the Faculty of Health Sciences (FCCSS) of the Technical University of Babahoyo (UTB); At the same time, a state of simulation will be represented with the data collected through the research technique based on direct observation In Situ. With the results obtained, an analysis with high technical content will be developed in which the security levels of the data network of the Faculty of Health Sciences (FCCSS) are verified; for this, it will be necessary to use software related to the study area with the aim of acquiring an x-ray of the communication systems and their methods used for the detection of vulnerabilities in the data network; the level of penetration in the student, teaching and administrative community is verified, trying to potentiate the existing infrastructure and information technology (IT) with a new network model oriented to the scaling of the medium and physical level, routing and signaling of traffic, multiplexing and size of communication windows, multiple access and convergent to the node main, networks and trunks, digital transmission and WiFi networks.